Aquatic Exercise and Other Physical Therapies for Knee Osteoarthritis: A Narrative Review of Clinical Efficacy, Mechanisms and Future Perspectives - Tu, Hanrui (International Journal of Public Health and Medical Research, 2026)
Knee osteoarthritis (OA) is a common disease, especially among the elderly, and poses a serious global health burden. This review aims to analyze the clinical efficacy of aquatic exercise and other physical therapies in the treatment of knee osteoarthritis, focusing on its mechanism of action, efficacy and future prospects. The review emphasizes the role of aquatic exercise. Due to the buoyancy and resistance of water, water exercise provides a low-impact but effective treatment that can reduce pain, improve function and enhance joint stability. This review compares water exercise with other non-drug treatments, such as land-based exercise, manual therapy and electrotherapy, to evaluate their biomechanical and physiological effects. Although clinical research results generally support the value of water therapy, its benefit mechanism and its impact on joint load, muscle activation and exercise efficiency are not fully clarified. Filling these research gaps is crucial to the development of more personalized and sustainable rehabilitation programs. This review further explores the potential role of emerging technologies, including wearable sensors and digital monitoring tools, in promoting precise rehabilitation. In addition, this article also discusses the future development direction, emphasizes the importance of long-term clinical trials, and the necessity of combining biomechanics and biomedical engineering to improve and optimize the physical therapy strategy for patients with knee osteoarthritis.